2022
DOI: 10.3390/ijms23073902
|View full text |Cite
|
Sign up to set email alerts
|

GABAA Receptor-Stabilizing Protein Ubqln1 Affects Hyperexcitability and Epileptogenesis after Traumatic Brain Injury and in a Model of In Vitro Epilepsy in Mice

Abstract: Posttraumatic epilepsy (PTE) is a major public health concern and strongly contributes to human epilepsy cases worldwide. However, an effective treatment and prevention remains a matter of intense research. The present study provides new insights into the gamma aminobutyric acid A (GABAA)-stabilizing protein ubiquilin-1 (ubqln1) and its regulation in mouse models of traumatic brain injury (TBI) and in vitro epilepsy. We performed label-free quantification on isolated cortical GABAergic interneurons from GAD67-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
(126 reference statements)
0
1
0
Order By: Relevance
“…The decrease in Ubqln1 and impaired GABAergic interneurons result in reduced inhibitory effects of GABAergic interneurons, leading to increased neuronal excitability and heightened susceptibility to epilepsy [ 45 ]. In an in vitro epilepsy model, researchers have found that using niacinamide (NM) to increase Ubqln1 expression can stabilize GABA A receptors to relieve the generation of epileptiform activity [ 46 ], suggesting that modulating Ubqln1 could be a potential strategy for alleviating the epileptogenesis.…”
Section: Molecular Mechanisms and Potential Drug Targets During Epile...mentioning
confidence: 99%
“…The decrease in Ubqln1 and impaired GABAergic interneurons result in reduced inhibitory effects of GABAergic interneurons, leading to increased neuronal excitability and heightened susceptibility to epilepsy [ 45 ]. In an in vitro epilepsy model, researchers have found that using niacinamide (NM) to increase Ubqln1 expression can stabilize GABA A receptors to relieve the generation of epileptiform activity [ 46 ], suggesting that modulating Ubqln1 could be a potential strategy for alleviating the epileptogenesis.…”
Section: Molecular Mechanisms and Potential Drug Targets During Epile...mentioning
confidence: 99%